Low expression of Abelson interactor-1 is linked to acquired drug resistance in Bcr-Abl induced leukemia - Chorzalska, Anna (2014)
The basis for persistence of leukemic stem cells in the bone marrow microenvironment (BMME) remains poorly understood. We present evidence that signaling crosstalk between α4 integrin and Abelson interactor-1 (Abi-1) is involved in acquisition of an anchorage-dependent phenotype and drug resistance in Bcr-Abl positive leukemia cells. Comparison of Abi-1 (ABI-1) and α4 integrin (ITGA4) gene expression in relapsing Bcr-Abl positive CD34+ progenitor cells demonstrated a reduction in Abi-1 and an increase in α4 integrin mRNA in the absence of Bcr-Abl mutations. This inverse correlation between Abi-1 and α4 integrin expression, as well as linkage to elevated phospho-Akt and phospho-Erk signaling, was confirmed in imatinib mesylate (IM) resistant leukemic cells. These results indicate that the α4-Abi-1 signaling pathway may mediate acquisition of the drug resistant phenotype of leukemic cells.